MORPHOLOGICAL FEATURES OF NEURONS INNERVATING DIFFERENT PARTS OF THE LARGE INTESTINE - Babaeva, R.E. (World of Medicine and Biology, 2021)
The purpose of the study was to obtain complex morphological data on neurons innervating different parts of the large intestine. The object of the study was rats (n=17) of the Wistar line. The study used a universal method of impregnation. In addition, a 3D model of neurocytes of the ganglia of the intermuscular plexus of the large intestine was made. The results of the study showed that the large intestine has intra-organ ganglia located in the intermuscular and submucosal plexuses. The intermuscular plexus (Auerbach) of the colon has the form of a network with cells of different shapes and consists of nerve nodes containing Dogel cells of the 1st and 2nd type. In the intramural nodes of the large intestine, there are a large number of sensitive nerve endings. At the same time, a significant number of these endings in the nodes are formed by the processes of type 2 Dogel cells. A study of a three – dimensional image of a type 2 Dogel cell from the intermuscular plexus of the large intestine showed that this cell has an ovoid shape. The cell is flattened transversely and elongated longitudinally. The volume of its pericaryon is 2785.11 µm3, the volume of the nucleus is 647.7 µm3.